Longitudinal study of physical activity using an accelerometer in Japanese pregnant women. Issue 2 (29th August 2019) - Kawajiri, Maiko; Nakamura, Yasuka; Takeishi, Yoko; Ito, Naoko; Atogami, Fumi; Yoshizawa, Toyoko
Abstract: Aim: To describe the characteristics of objectively measured physical activity (PA) during the 2nd and 3rd trimesters of pregnancy using a accelerometer. Methods: This was a longitudinal observational study wherein PA in pregnant women in the 2nd and 3rd trimesters was measured for seven consecutive days using a accelerometer (Silmee W10, TDK, Japan). Results: A total of 34 primiparous women were examined. There was no statistically significant difference in the amount of PA during the 2nd and 3rd trimesters of pregnancy. Sub‐group analysis demonstrated that PA in the full‐time housewife group increased significantly from the 2nd to the 3rd trimester, while total PA and moderate and vigorous PA of the stopped‐working group, decreased significantly over that time. There was no difference in the PA of the currently working group between trimesters. In the full‐time housewife group, the amount of PA for each hour significantly increased at 12:00, 18:00, and 22:00 hr. In the currently working group, the amount of PA for each hour significantly increased at 9:00, 10:00, and 16:00 hr. In the stopped‐working group, the amount of PA for each hour significantly decreased at 7:00, 8:00, and 18:00 hr. Conclusion: Objective measurements using an accelerometer did not identify any significant changes in PA during the different trimesters of pregnancy. Sub‐group analysis revealed clear patterns in PA change correlating with different lifestyles during pregnancy. Future research may enable the development of personalized health guidance by identifying the relationship between PA and pregnancy outcomes.